Investigation of curing effects on distortion of fibre metal laminates. (April 2015) - Abouhamzeh, M.; Sinke, J.; Benedictus, R.
Abstract: In this paper, the curing process of FMLs is investigated as part of a research on modelling the (elastic) response upon manufacturing. The curing process results in shape deviations and residual stresses. In order to build a predictive model, the curing process should be studied with modelling and experiments. Here, an investigation of the distortion generated in the cure cycle of FMLs is performed which can be used to improve the design of FMLs for fatigue, damage tolerance and residual strength. Non-symmetric panels are made which have a curvature after cure. The determination of the elastic response (distortions and residual stresses) is based on reheating the un-symmetric laminate combined with strain measurement until a balance exists among thermal forces in the layers and the laminate becomes flat (free of bending strain). The so-called bending strain-free temperature deviates significantly from the cure temperature for different panels. This difference is due to the "curing effects" including chemical shrinkage and change of resin properties during cure. A thermoelastic model is developed based on classical laminate theory (CLT) and comparison with the experimental results shows the modelling accuracy and the needed improvements for prediction of the residual stresses and final distortions.